Streaming Potential - Edmark, K.W; Davis, J; Milligan, H.L (Thrombosis and Haemostasis, 1970)
Bioelectric charge transfer at the blood-wall interface may be a crucial factor affecting thrombosis on implant materials. The in-vitro streaming potential test technique offers a very sensitive, yet simple, means for observing this interfacial electrokinetic charge phenomena. Particular attention to test control variables is required, however, to obtain valid, comparative results. Due to the dynamic, changing nature of some surfaces on the molecular scale, reproducibility of results is subject to question and necessitates repeated runs to gain assurance of results.It is demonstrated that this method of evaluation is an extremely sensitive tool in the study of blood-surface inter-actions. Changes in streaming potentials are dramatically revealed upon introduction of minute quantities of blood protein elements and drugs affecting blood coagulation. The techniques for applying this test method to the study of thrombosis are illustrated.Streaming potential testing is a possible tool for realizing quality control in the preparation of anti-thrombogenic materials for cardiovascular implants. It may serve as a check, both on the formation of a proper surface and on the stability of this surface under physiological environment conditions.